2021
DOI: 10.3390/systems9040078
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Perspective to Support Decision Making in Structural Retrofitting of Buildings: A Case Study

Abstract: The reuse of existing materials in buildings can give a contribution to sustainable practices such as a balance in embodied energy, water, and emission reduction. However, it is not always possible to maintain the existing structural materials because some different technical variables could hamper their usability, namely seismic reinforcement needs, fire safety protection, conservation state, and new legal requirements. The paper follows a case study approach for assessing the technical and environmental perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Alabid et al reviewed the energy retrofitting-related policies of old buildings currently adopted in the UK to reduce GHG emissions and recommended the implementation of various policies and standards to achieve improvement in stages [21]. Oliveira et al evaluated the technical and environmental performance of structural options based on an environmental impact assessment of several categories of structural retrofitting of old buildings [22]. Vita et al examined the possibility of improving energy efficiency (U-value) using reinforcing materials in the seismic retrofitting of masonry walls for historical stone buildings in Italy [23].…”
Section: Introduction 1background and Objectives Of The Studymentioning
confidence: 99%
“…Alabid et al reviewed the energy retrofitting-related policies of old buildings currently adopted in the UK to reduce GHG emissions and recommended the implementation of various policies and standards to achieve improvement in stages [21]. Oliveira et al evaluated the technical and environmental performance of structural options based on an environmental impact assessment of several categories of structural retrofitting of old buildings [22]. Vita et al examined the possibility of improving energy efficiency (U-value) using reinforcing materials in the seismic retrofitting of masonry walls for historical stone buildings in Italy [23].…”
Section: Introduction 1background and Objectives Of The Studymentioning
confidence: 99%
“…Many studies reported the efforts of HEIs in these aspects, including the realization of campus energy conservation [11,12], sustainable resource usage [13,14], environment performance [15], etc. More up-to-date research covers carbon neutralization [16,17] and near-zero energy consumption [18,19] renovation in HEI campus.…”
Section: Introductionmentioning
confidence: 99%